Em busca da escola unitária: entraves e perspectivas para a formação integrada nos institutos federais - Amorim, Gilberto José (2023)
Through this research, the aim was to understand the type of integrated high school education that federal institutes are offering to Brazilian youth: whether it falls under a liberal perspective, which only seeks to qualify the workforce, or whether it can be seen from a progressive perspective, which seeks to contribute to a humanistic education. Additionally, the study sought to investigate how Gramscian theory was incorporated into the theses and dissertations produced by federal institute employees who studied integrated high school education. The reasons why young people enroll in these courses were also analyzed. To achieve this, the research used theses and dissertations produced by institution employees who studied the topic between the years of the creation of federal institutes and the approval of the high school counter-reform by the Temer government (2008-2017) as a source. These works helped to understand the concept of these researcher-employees regarding integrated high school education and to what extent the high school proposal being implemented can be seen as a transition to a unified school and omnilateral education, or if, despite the desires of its creators, the project has been reduced in reality to workforce qualification for the current stage of Brazilian capitalism development. Thus, through the theses and dissertations of these researcher-employees, it was observed that Gramsci's thought, as well as the concept of integrated education, were conceived in different ways, serving both for the planning of a humanistic high school education and for its connection to market needs. Additionally, it was possible to perceive that young people enroll in integrated high school education with the goal of continuing their studies at the university level. In this perspective, it was possible to understand the way in which integrated high school education is being implemented in the institutes and, therefore, to contribute to the construction of a quality high school education for all Brazilian youth